2010
DOI: 10.2320/matertrans.p-m2010817
|View full text |Cite
|
Sign up to set email alerts
|

Elasto-Plasticity Behavior of High Strength Steel Sheet in Biaxial Stress Path Change

Abstract: The elasto-plasticity behavior of a high-strength steel sheet of 980 MPa-TS was investigated by performing biaxial tension experiments. In order to evaluate the accuracy of constitutive models of plasticity in describing such elasto-plasticity behavior, numerical simulations of stressstrain responses were conducted for the same stress paths as those in the experiments using two types of constitutive models: the isotropic hardening model (IH model) and the kinematic hardening model proposed by the present autho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
1
0
Order By: Relevance
“…It is found the experimental data of cross effect show very complicated stress–strain responses . While the stress–strain responses in both 45° and 90° direction with 5% plastic pre‐strain do not show the yield plateau after re‐yielding, the stress–strain responses in the two directions with 10% plastic pre‐strain shows the yield plateau after stress‐reversal.…”
Section: Resultsmentioning
confidence: 93%
“…It is found the experimental data of cross effect show very complicated stress–strain responses . While the stress–strain responses in both 45° and 90° direction with 5% plastic pre‐strain do not show the yield plateau after re‐yielding, the stress–strain responses in the two directions with 10% plastic pre‐strain shows the yield plateau after stress‐reversal.…”
Section: Resultsmentioning
confidence: 93%
“…Yield Loci. Generally yield locus (equi-plastic work surface) of sheet metal is determined by performing biaxial tension test using a cruciform specimen [5]. However, biaxial tension test of perforated sheet is not easy because of non-uniform stress/strain distribution in a gauge section.…”
Section: Plastic Deformation In Uniaxial/biaxial Tensionmentioning
confidence: 99%
“…An appropriate choice of the combination of constitutive model is of vital important for an accurate sheet-metal stamping simulation [1][2][3] For that purpose, "Yoshida-Uemori model" has been proposed and its high capability in simulating cyclic behavior. The model has been already verified by comparing the numerical simulations with several evidences [4][5][6][7]. However, it was found that the verification of this model, especially the details of the non-proportional deformation behaviors, is not guaranteed for low yield point materials.…”
Section: Introductionmentioning
confidence: 99%